Impact of anti-money laundering regulations on art business in the European Union - Reķe-Luste, Zane (Riga Graduate School of Law, 2018)
The thesis researches and analyses reasons, why is art market attractive for money laundering and a safe haven for dubious players. It also suggests that the laws should be changed to combat money laundering through art markets more effectively.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Money laundering; Art market